A new species of Psidium and notes on Neomitranthes from the state of São Paulo, Brazil - Maruyama, Adriano Da Silva De Cicco; Tuler, Amélia Carlos; Valdemarin, Karinne S.; Proença, Carolyn Elinore Barnes; Mazine, Fiorella Fernanda (Phytotaxa, 2024)
Psidium riobonito, a new species of Myrtaceae from the Atlantic Forest of the northeastern portion of the Brazilian state of São Paulo, was collected in High Montane Dense Ombrophilous Forest and is described here. Morphological characters assign the new species to Psidium sect. Apertiflora, due to its leaves with brochidodromous veins, marginal vein parallel to the margin, inflorescences in auxotelic racemes, flowers with open buds with 5 calyx lobes, in addition to dark purple fruits when ripe, with few seeds. Psidium riobonito is morphologically close to P. involutisepalum and P. myrtoides, but differs by the marginal veins 2 to 5 mm from the margin (vs. 1 to 2 mm in P. myrtoides and 1.5 to 2 mm in P. involutisepalum), glabrous or glabrescent leaves when mature (vs. pubescent or sparsely pubescent mainly along the midrib on the abaxial surface in P. myrtoides and sparsely pubescent in P. involutisepalum), pedicels 14–26 mm long (vs. 3–12 mm in P. myrtoides and 8–10 mm in P. involutisepalum). The relationship of P. riobonito to morphologically close species, comments on its taxonomy, ecology and informal conservation status, and a table with morphological characteristics of P. sect. Apertiflora are also provided. We also present for the first time the descriptions of the fruits of Neomitranthes capivariensis and N. pedicellata.